2016
DOI: 10.1002/cre2.41
|View full text |Cite
|
Sign up to set email alerts
|

Porphyromonas gingivalis induced periodontitis exacerbates progression of non‐alcoholic steatohepatitis in rats

Abstract: Non‐alcoholic steatohepatitis (NASH) is a chronic liver disease that can develop into hepatocirrhosis and hepatic carcinoma. In recent years, epidemiological and animal studies have reported that Porphyromonas gingivalis (P. gingivalis), a known periodontopathic bacteria, is closely related to NASH. However, previous studies could not demonstrate a direct relationship between periodontitis, P. gingivalis infection, and NASH. The purpose of the present study was to examine the impact of P. gingivalis‐associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 38 publications
1
47
1
Order By: Relevance
“…Previous epidemiologic and animal studies have reported that P. gingivalis , a primary periodontopathic bacterium, plays an important role in the relationship between periodontitis and NASH . We have demonstrated that experimental P. gingivalis periodontal infection led to NASH progression in rats with fatty liver . Although P. gingivalis was not observed in either the blood or liver, significant levels of endotoxin were detected in the blood.…”
mentioning
confidence: 59%
See 2 more Smart Citations
“…Previous epidemiologic and animal studies have reported that P. gingivalis , a primary periodontopathic bacterium, plays an important role in the relationship between periodontitis and NASH . We have demonstrated that experimental P. gingivalis periodontal infection led to NASH progression in rats with fatty liver . Although P. gingivalis was not observed in either the blood or liver, significant levels of endotoxin were detected in the blood.…”
mentioning
confidence: 59%
“…Previous animal experiments showed that the intravenous injection and application of P. gingivalis via the dental pulp exacerbated steatohepatitis in HD fed mouse models. Further, we reported that a P. gingivalis infection model of periodontitis in HD rats induced the onset of NASH, and we also proposed that P. gingivalis as well as its LPS play an important role in the relationship between periodontitis and NASH …”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Measurement conditions for micro‐CT were as follows: tube voltage, 65 kV; electrical current, 80 μA; image pixel size, 1024 × 1024; and slice thickness, 15 μm. After scanning, 3‐dimensional (3D) images were reconstructed using TRI/3D‐BON version 64 software (Ratoc System Engineering, Tokyo, Japan) in three regions (mesial, central, and distal sites) of the M1 (Figure A), the distance from the palatal cemento‐enamel junction (CEJ) to the alveolar bone crest (ABC) was measured as previously described . The average of the three distances was defined as the representative value for each rat.…”
Section: Methodsmentioning
confidence: 99%
“…After scanning, 3-dimensional (3D) images were reconstructed using TRI/3D-BON version 64 software (Ratoc System Engineering, Tokyo, Japan) in three regions (mesial, central, and distal sites) of the M1 (Figure 2A), the distance from the palatal cemento-enamel junction (CEJ) to the alveolar bone crest (ABC) was measured as previously described. 32 The average of the three distances was defined as the representative value for each rat. The volumetric measurement of furcation was performed after the selection of a region of interest (ROI), which was selected according to the following standardized dimensions and anatomical landmarks: (a) a line 0.5 mm apical to the CEJ of the first molar as the coronal limit extended vertically 1 mm to the root apical, (b) a line 3 mm with the mesial-distal dimension from the mesial CEJ of the first molar, and (c) a line 2.5 mm with the buccal-palatal dimension ( Figure 2B).…”
Section: Micro-computed Tomography Analysismentioning
confidence: 99%